2015
DOI: 10.1007/s10735-015-9625-4
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin alleviates experimental diabetic cardiomyopathy by suppressing apoptosis and oxidative stress

Abstract: Diabetic hazard on the myocardium is a complication of diabetes that intensifies its morbidity and increases its mortality. Therefore, alleviation of diabetic cardiomyopathy (DCM) by a reliable drug remains a matter of interest in experimental research. The aim of this study was to explore the structural alterations in the myocardium induced by atorvastatin (ATOR) in DCM, induced by streptozotocin (STZ), along with the associated changes occurring in apoptosis and oxidative stress markers. Thirty-two rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 44 publications
(58 reference statements)
3
13
0
Order By: Relevance
“…In recent studies, the drug alleviated progression of experimental DCM, possibly by a protective effect against apoptosis, independent of its LDL-cholesterol-lowering properties [14]. We demonstrated in this study that the anti-apoptotic and cardioprotective effects of ATOR may be explained by inhibition of sustained activation of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In recent studies, the drug alleviated progression of experimental DCM, possibly by a protective effect against apoptosis, independent of its LDL-cholesterol-lowering properties [14]. We demonstrated in this study that the anti-apoptotic and cardioprotective effects of ATOR may be explained by inhibition of sustained activation of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 50%
“…Mice were sacrificed and their hearts harvested and fixed in 4% paraformaldehyde, embedded in paraffin and sectioned (3–4 μm thickness) [14]. After dehydration, sections were stained with hematoxylin-eosin (H-E) and prepared for Masson's trichrome staining.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of cardiomyocyte death parallels the severity of the diabetic cardiomyopathy and its stage of evolution [7]. Attenuation of cardiomyocyte apoptosis has been shown to prevent diabetic cardiomyopathy [8, 9]. The mechanisms of apoptosis involved in diabetic cardiomyopathy are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…33 AbdelHamid et al also suggested that atorvastatin could preserve myocardial structure in diabetic cardiomyopathy by suppressing cardiomyocyte apoptosis and oxidative stress. 34 These results indicate that atorvastatin has heartprotective effects from oxidative stress. The findings of our study indicate that TNF-a induced by hypoxia is inhibited by atorvastatin.…”
Section: Discussionmentioning
confidence: 82%